The Controversy of Child Marriage Culture in The Perspective of Maqāṣid al-Usrah: A Case Study of The Authority of Lebe' in Brebes - Aprilianto, Dwi; Na'imah, Farida Ulvi; Fauzi, Ahmad; Maknuun, Lu’lu’ il (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This research is backdroped by the role of Kiais (religious figures) whose opinions regarding the permissibility of child marriage are widely followed by their local community. It aims to investigate the relevance of child marriage law in the Regency of Brebes from the perspective of maqāṣid al-usrah. This research was conducted in Banjarharjo, Pararaja, Banjaran, and Brebes districts of the Regency of Brebes by employing legal anthropology and Ushul al-Fiqh approaches. The theories used in this research are internalization theory and maqāṣid al-usrah. Data were collected through interviews, observations, and document analysis. The practice of child marriage in Brebes society is, in principle, irrelevant to the concept of maqāṣid al-usrah, which was theoretically explained by Jamal al-Din 'Aṭiyyah. This research found that religious understanding that is internalized in the community traditions resulted in a fiqh product entitled Kitāb al-Nikah authored by an Indonesian ulama and the authority of Lebe' which has had a significant influence on the practice of child marriage in Brebes Regency. The practice of child marriage should not only be based on authoritative texts but also requires consideration of 'āqil bāligh as well as consideration of suitability, namely rushd (capability) as well as considering maqāṣid al-usrah, regulating the relationship between men and women (tanẓīm al-'alaqah bayn al-jinsayn), realization of peace, love, and compassion (taḥqīq al-sakn wa al-mawaddah wa al-raḥmah), maintaining religion in the family (hifz al-tadayyun fi al-usrah), regulating the essential aspects of the family (tanẓīm al-jānib al-mu'assasī li al-usrah), and Family Financial Regulation (tanẓīm al-jānib al-māl li al-usrah).